Role of Bevacizumab (Avastin) in Diabetic Macular Edema (Medical Forum Monthly, 2021)
Objective: To evaluate the efficacy of injection Bevacizumab (Intravitreal) in management of diabetic macular edema (DME).Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the completed at Ophthalmology department Nishtar Hospital Multan from March 2019 to March 2020.Materials and Methods: Study was conducted on 60 eyes of 60 patients presented with diabetic macular edema. Intravitreal bevacizumab injection of 1.25 mg was administered 3.5 mm from the limbus under topical anesthetic drops. Follow up was done at 1st day and at 1 month duration after injection. Macular thickness was measured at every follow ups visit. SPSS version 23 was used for analysis of data. P value ≤ 0.05 was considered as significant.Results: The mean pre Avastin macular thickness of the patients was 391.43±30.91 µm and after Avastin OCT at one month was 308.66±25.82 µm. Difference was found significant statistically, (p=0.000).Conclusion: Diabetes leads to macular edema and retinopathy which is a hurdle in macular grid laser in such cases. Intravitreal injection of bevacizumab minimizes the exacerbation of macular edema in diabetic cases.